Probabilistic examination of the change in eigenfrequencies of an offshore wind turbine under progressive scour incorporating soil spatial variability - Prendergast, L.J.; Reale, C.; Gavin, K. (Elsevier, 2018)
The trend for development in the offshore wind sector is towards larger turbines in deeper water. This results in higher wind and wave loads on these dynamically sensitive structures. Monopiles are the preferred foundation solution for offshore wind structures and have a typical expected design life of 20 years. These foundations have strict serviceability tolerances (e.g. mudline rotation of less than 0.25° during operation). Accurate determination of the system frequency is critical in order to ensure satisfactory performance over the design life, yet determination of the system stiffness and in particular the operational soil stiffness remains a significant challenge. Offshore site investigations typically focus on the determination of the soil conditions using Cone Penetration Test (CPT) data. This test gives large volumes of high quality data on the soil conditions at the test location, which can be correlated to soil strength and stiffness parameters and used directly in pile capacity models. However, a combination of factors including; parameter transformation, natural variability, the relatively small volume of the overall sea bed tested and operational effects such as the potential for scour development during turbine operation lead to large uncertainties in the soil stiffness values used in design. In this paper, the effects of scour erosion around unprotected foundations on the design system frequencies of an offshore wind turbine is investigated numerically. To account for the uncertainty in soil-structure interaction stiffness for a given offshore site, a stochastic ground model is developed using the data resulting from CPTs as inputs. Results indicate that the greater the depth of scour, the less certain a frequency-based SHM technique would be in accurately assessing scour magnitude based solely on first natural frequency measurements. However, using Receiver Operating Characteristic (ROC) curve analysis, the chance of detecting the presence of scour from the output frequencies is improved significantly and even modest scour depths of 0.25 pile diameters can be detected.